2019
DOI: 10.1002/psc.3155
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic stability of macrocyclic peptide triazole HIV‐1 inactivators alone and in liposomes

Abstract: Previously, we reported the discovery of macrocyclic peptide triazoles (cPTs) that bind to HIV‐1 Env gp120, inhibit virus cell infection with nanomolar potencies, and cause irreversible virion inactivation. Given the appealing virus‐killing activity of cPTs and resistance to protease cleavage observed in vitro, we here investigated in vivo pharmacokinetics of the cPT AAR029b. AAR029b was investigated both alone and encapsulated in a PEGylated liposome formulation that was designed to slowly release inhibitor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Without chemical modifications, peptides have a short circulating half-life of several minutes. They are rapidly degraded by protease enzymes (29)(30)(31) and eliminated by renal filtration (50). We recognized that a peptide's rapid renal clearance could be advantageous as a drug carrier to dispose most systemically administered drugs in urine for treating NMIBC and reducing the unwanted systemic side-effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without chemical modifications, peptides have a short circulating half-life of several minutes. They are rapidly degraded by protease enzymes (29)(30)(31) and eliminated by renal filtration (50). We recognized that a peptide's rapid renal clearance could be advantageous as a drug carrier to dispose most systemically administered drugs in urine for treating NMIBC and reducing the unwanted systemic side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…Further, without chemical modifications, a peptide is not a good drug candidate or carrier. It displays unfavorable pharmacokinetics (PK), is rapidly degraded by protease enzymes (29)(30)(31), and can be eliminated by renal filtration. In the present studies, we exploited a peptide's Research.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Yoshida et al reported the solid-phase synthesis and bioactivity evaluation of cherimolacyclopeptide E [ 77 ]. Additional on-resin MW-assisted macrocyclization of peptides via amide coupling was reported by Rashad et al in 2015 [ 78 ] and Aneja et al in 2019 [ 79 ].…”
Section: Microwave-assisted And/or Solid-supported Synthesis Of Macro...mentioning
confidence: 98%
“…Besides the abovementioned 1,2,3‐triazole–peptide hybrids, some other peptides could serve as potential entry inhibitors binding to HIV‐1 gp120. [ 74–79 ] Among them, the 1,2,3‐triazole–macrocyclic peptide hybrid 27 (EC 50 : 105 nM), which showed enhanced entropically favored binding to Env gp120, was highly active against HIV‐1 BAL strain, so this hybrid warrants further study. [ 79 ]…”
Section: 23‐triazole–peptide Hybridsmentioning
confidence: 99%